ANALISIS KINERJA DAN STUDI KELEMBAGAAN PASAR IKAN HIAS PARUNG, KABUPATEN BOGOR (Kasus: Ikan Cupang) - Cita Nabila Thabrani; Suharno Suharno; Siti Jahroh (Jurnal Sosial Ekonomi Pertanian, 2019)
AbstractPasar Parung as a private market established without government interference and relying only on citizen initiatives developed into a very good market when compared to government markets that have been fully supported facilities and operations. This inequality leads to the need for evaluation in terms of market performance Parung. Parung market performance measurement is done by SCP (performance behavior structure) and Sub Terminal Agribusiness method. The market structure Parung approaches the perfect market competition structure (PPS) with a normal market share. There are 5 channels detected through Parung market. With a large margin of Rp 5645 and farmer's share of 30.46% and profit ratio of 1.49. Pasar Parung has not been able to fulfill the absolute requirement of the government's ideal market based on the concept of Sub Terminal of Agribusiness (STA), this is because the market owner is considered not having a good enough understanding in the establishment of a good market according to STA establishment standardsKeywords: Structure of Behavior and Performance, Market Parung, Ornamental Fish, Sub Terminal Agribusiness